Publication Trends of Research on Polypoidal Choroidal Vasculopathy During 2001–2020: A 20-Year Bibliometric Study - Wang, Yimin; Xie, Minyue; Zhang, Min; Zhao, Xiaohuan; Zhu, Xinyue; Wang, Yuwei; Chen, Yuhong; Chen, Jieqiong; Sun, Xiaodong (Frontiers in Medicine, 2022)
Introduction Polypoidal choroidal vasculopathy (PCV) is a special subtype of AMD, which is one of the leading threats to vision health worldwide. At this time, many aspects of PCV, from how it works to potential treatments, remain a mystery. In this study, we explored the frontier researches and revealed the study trends within the study of PCV. Methods We collected all the publications in this field from 2001 to 2020, analyzed trends within them, and defined the contributions of various countries/regions, institutions, authors, and journals. Additionally, VOSviewer software was used to define the hot keywords in this field. Results A total of 1,190 publications were ultimately examined; We found that PCV is becoming an increasingly relevant topic of research, and that Japan has contributed the most publications (428), the most citations (14,504 in total), and the highest H-index value (62) to the field. Our keywords analysis was classified into four clusters to show the hotspots within the study of PCV, namely mechanism-related, imaging-related, prognosis-related, and therapy-related topics. The average years in which the keywords appeared the most were also calculated, and we identified anti-VEGF therapy, anti-complement therapy and angiography as having been the main focus in recent years. Conclusions These results helped clarify the comprehensive research progress that has been made as well as the future trends in the study of PCV, which can assist and guide future research.